1998
DOI: 10.1073/pnas.95.15.8801
|View full text |Cite
|
Sign up to set email alerts
|

Myocyte proliferation in end-stage cardiac failure in humans

Abstract: Introduced several decades ago, the dogma persists that cardiac myocytes are terminally differentiated cells and that division of muscle cells is impossible in the adult heart. More recently, nuclear mitotic divisions in myocytes occasionally were seen, but those observations were challenged on the assumption that the rate of cell proliferation was inconsequential for actual tissue regeneration. Moreover, mitoses were never detected in normal myocardium. However, the analysis of routine histologic preparations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
285
0
10

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 495 publications
(304 citation statements)
references
References 25 publications
9
285
0
10
Order By: Relevance
“…This is in contrast with asymmetric cellular hypertrophy in pressure overload model (Campbell et al, 1989), where most pronounced hypertrophy was found in the subendocardial layers. The interesting discrepancy between continued increase in ventricular wall thickness that could not be explained by increased myocyte dimensions, especially in the right ventricle (Table 2) suggests, in the notable absence of fibrosis, that there could be activation of myocyte (or resident stem cells) proliferation, that was recognized previously in decompensated HF in humans (Kajstura et al, 1998).…”
Section: Discussionmentioning
confidence: 76%
“…This is in contrast with asymmetric cellular hypertrophy in pressure overload model (Campbell et al, 1989), where most pronounced hypertrophy was found in the subendocardial layers. The interesting discrepancy between continued increase in ventricular wall thickness that could not be explained by increased myocyte dimensions, especially in the right ventricle (Table 2) suggests, in the notable absence of fibrosis, that there could be activation of myocyte (or resident stem cells) proliferation, that was recognized previously in decompensated HF in humans (Kajstura et al, 1998).…”
Section: Discussionmentioning
confidence: 76%
“…A myocyte mitotic index of 0.0014% in control hearts and 0.013% to 0.015% in diseased hearts was determined by confocal analysis. 2 Those initial data were confirmed and amplified in an autopsy study of human hearts 3 in which actively dividing cardiomyocytes (evidenced by Ki67 expression, a nuclear antigen expressed in dividing cells 4 ) resulted in mitotic indices of 0.08% and 0.03% in the regions adjacent to and distant from the infarcts, respectively. In principle, mitotic figures in the heart could arise from preformed cardiomyocytes released from cell cycle inhibition or from resident cardiomyocyte precursors or stem cells that become activated.…”
Section: Introductionmentioning
confidence: 86%
“…Mitotic CMN index was calculated according to previously described procedures for dog 16 and human 13,17 hearts. The numerical density of CMN per unit area of myocardium was obtained in each heart by counting in a 5 mm 2 area of the lateral wall mesocardium the number of CMN in longitudinally oriented cells containing sarcomeric a-actin.…”
Section: Mitotic Cmn Indexmentioning
confidence: 99%